ROLE OF ALLOGRAFTS IN THE MANAGEMENT OF MASSIVE APLASIA CUTIS CONGENITA OF SCALP - Hemant Saraiya (Indian Journal of Plastic Surgery)
A case of Aplasia Cutis Congenita with massive skin and bony defects on the vertex of the skull and the lumbo sacral region is presented The raw areas which were exposing the dura were treated by repeated application of allograft skin from the second day of life. Healing was achieved in 35 days without any problem. New bone formation with significant reduction of bony defect was noticed when the child was reviewed at 5 years.